PENGARUH SIKAP DAN KEMAMPUAN AKSES INTERNET TERHADAP HASIL BELAJAR KIMIA PESERTA DIDIK SMA NEGERI 6 KUPANG - MARSELINUS TIKA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of the study was to determine the effect of attitudes and internet access abilities on students' learning outcomes in Chemistry. This research is a quantitative study, using a survey method. The survey was conducted on a sample of 104 students of class XII MIPA SMA Negeri 6 Kupang. The data was collected by giving a questionnaire and by carrying out a test of chemistry learning outcomes. The results showed that the attitude variables in chemistry subjects and the ability to access the internet for online learning media together had a significant influence on students' chemistry learning outcomes. This is indicated by the coefficient of determination R2 = 0.790 with a constant test value (0.470). While the test of each regression coefficient of the attitude variable in chemistry subjects obtained a regression coefficient of (0.496) and the variable of internet access ability (0.516). From these results, it can be concluded that the attitudes and abilities of internet access for online learning media together have a significant influence on students' learning outcomes of chemistry. ABSTRAKTujuan dari penelitian adalah untuk mengetahui pengaruh sikap dan kemampuan akses internet terhadap hasil belajar Kimia peserta didik.Penelitian ini merupakan penelitian kuantitatif, menggunakan metode survei.Surve. Pengumpulan data dilakukan dengan pemberian kuesioner dan dengan melaksanakan test hasil belajar Kimia. Hasil penelitian menunjukkan bahwa variabel sikap pada mata pelajaran kimia dan kemampuan akses internet untuk media pembelajaran online secara bersama-sama memiliki pengaruh yang signifikan terhadap hasil belajar kimia peserta didik. Hal ini ditunjukkan oleh koefisien determinasi R2 = 0,790 dengan nilai uji constant (0,470). Sementara uji masing-masing koefisien regresi variabel sikap pada mata pelajaran kimia diperoleh koefisien regresi sebesar (0,496) dan variabel kemampuan akses internet (0,516). Dari hasil tersebut diperoleh kesimpulan bahwa sikap dan kemampuan akses internet untuk media pembelajaran online secara bersama-sama memiliki pengaruh yang signifikan terhadap hasil belajar Kimia peserta didik.